JANUS KINASE ENZYME (JAK) INHIBITORS AND RHEUMATOID ARTHRITIS: A REVIEW OF THE LITERATURE - ASKARI, AYMAN; NOURI, ABDULLA KHALID; MORRISSEY, HANA; BALL, PATRICK A. (International Journal of Current Pharmaceutical Research, 2019)
Cytokines play an essential role in normal cell growth and the regulation of immune function. The emergence of Janus Kinase Enzyme inhibitors promises the start of a revolution in the treatment of several chronic diseases. Their efficacy and safety profile have been demonstrated in multiple trials and they have been licensed for the treatment of a number of diseases including RA and PsA. Moreover, the use of highly selective Janus Kinase Enzyme inhibitors is currently being studied aiming to reduce side effects compared with traditional JAKinibs, an example of that would be the recent FDA approved upadacitinib. The Janus Kinase Enzyme inhibitorsmay supplant the classical biologic agents in the treatment of autoimmune diseases, since they exhibitthe advantages of oral administration, simultaneous blockade of multiple cytokines, reversibility and the lack of immunogenicity.